2018
DOI: 10.1055/s-0038-1660466
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Hospitalizations among U.S. Preterm Infants Compared with Term Infants Before and After the 2014 American Academy of Pediatrics Guidance on Immunoprophylaxis: 2012–2016

Abstract: Objective  The objective of this study was to compare risk for respiratory syncytial virus (RSV) hospitalizations (RSVH) for preterm infants 29 to 34 weeks gestational age (wGA) versus term infants before and after 2014 guidance changes for immunoprophylaxis (IP), using data from the 2012 to 2016 RSV seasons. Study Design  Using commercial and Medicaid claims databases, infants born between July 1, 2011 and June 30, 2016 were categorized as preterm or term. RSVH during the RSV season (November–March) were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…Our results are in line with those of previous analyses that found substantially decreased outpatient RSV IP use and increased RSVH risk among preterm infants after the AAP policy change. 9,[20][21][22] In single-center studies by Rajah et al and Blake et al, RSVH rates for preterm infants were significantly greater in post-versus pre-policy change RSV seasons. 9,21 Similarly, administrative claims analyses utilizing a patient population comparable to ours from the Truven Health MarketScan database showed that RSVH risk among preterm infants increased significantly in the 2014 to 2015 season compared with the 2013 to 2014 season, 20 and in the 2014 to 2016 seasons compared with the 2012 to 2014 seasons.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results are in line with those of previous analyses that found substantially decreased outpatient RSV IP use and increased RSVH risk among preterm infants after the AAP policy change. 9,[20][21][22] In single-center studies by Rajah et al and Blake et al, RSVH rates for preterm infants were significantly greater in post-versus pre-policy change RSV seasons. 9,21 Similarly, administrative claims analyses utilizing a patient population comparable to ours from the Truven Health MarketScan database showed that RSVH risk among preterm infants increased significantly in the 2014 to 2015 season compared with the 2013 to 2014 season, 20 and in the 2014 to 2016 seasons compared with the 2012 to 2014 seasons.…”
Section: Discussionmentioning
confidence: 94%
“…Several U.S. studies have demonstrated an increase in RSVH risk among infants 29 to 34 wGA and < 6 months CA under the more restrictive recommendations. 9,[20][21][22] These findings would benefit from validation in other large datasets. In addition, the effect of the policy change on RSVH severity and costs has not been evaluated.…”
mentioning
confidence: 81%
“…Additionally, three recent studies demonstrate the rate of RSVH in infants 29 to 34 wGA compared with term infants has increased since the release of the 2014 COID guidance. 27,29,30 Another limitation of this study is that although hospital charges are reported, actual reimbursement amounts may differ. Hospital charges reported here do not include physician fees and also do not account for reimbursements that are commonly negotiated between hospitals and insurance carriers.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Historically, the COID guidance recognized that preterm infants 29 to 35 wGA were at high enough risk to warrant RSV IP in certain circumstances that varied among iterations of the guidance. 98 (28) 99 (30) 197 2925 (13) 19 (10) 44 126 67 813 75 96 1111 (10) Abbreviations COID guidance statement, released in 2014, was the first to not recommend RSV IP for infants who were born at 29 to 35 wGA without comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…11 Two recent large retrospective studies using commercial and Medicaid insurance databases compared RSV hospitalization rates in premature infants before and after the 2014 AAP guidance change, and included healthy full-term infants as a reference. 12,13 Authors showed again that RSV-associated hospitalizations in infants born at 29 to 34 wGA and < 3 months of age increased up to 2.7-fold after the guidance change. They also showed that compared with fullterm infants, premature infants had up to seven times higher risk for RSV-associated hospitalizations.…”
Section: Current Trends In Rsv-associated Morbidity In Premature Infantsmentioning
confidence: 97%